Economic Growth: A Literature Review On Its Scope And Thematic Coverage - Devi Yuliana (International Journal of Economics, Science, and Education, 2025)
Company policies are instruments that regulate the running of an organization and serve as guidelines for all employees in carrying out their duties. These policies not only determine the company's operational direction but also influence employee behavior, motivation, and well-being. In the context of increasingly complex employment relationships, company policies have a significant impact on productivity and job satisfaction. Furthermore, policies also serve as a communication tool to ensure all individuals within the organization are working within the same framework. When policies are well- formulated, the work environment becomes more orderly, safe, and conducive to employee development.